Pengembangan Kemasan Produk Bawang Goreng Menggunakan Metode Value Engineering - Farhan Iman Mudzakir; Zulkarnain; Heribertus Rudi Kusumantoro (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The growth of the snack food industry in Indonesia encourages MSME actors to innovate in improving product competitiveness, including through packaging development. UMKM Nambawang, as a producer of fried shallots, faces challenges in packaging design that lacks visual appeal and does not reflect the product’s identity, despite its superior taste quality. This study aims to design more functional, economical, and competitive fried shallot packaging by integrating the Quality Function Deployment (QFD) and Value Engineering (VE) methods. QFD is applied to translate consumer needs (voice of customer) into technical packaging attributes, while VE is used to evaluate the performance and cost-efficiency of design alternatives. The analysis results indicate that key attributes prioritized in packaging development include color aesthetics, product protection, ease of opening and resealing, clarity of product information, and storage convenience. These main attributes are translated into technical elements such as the use of standing pouches, zipper locks, full-print designs, added onion illustrations, and complete product information. The application of QFD and VE methods results in a mockup visually appealing, functional, and durable packaging design, enhancing the product’s added value based on consumer needs and increasing its competitiveness in the domestic market.